(untitled) (European Journal of Pure and Applied Mathematics, 2022)
A set S ⊆ V (G) is a restrained strong resolving hop dominating set in G if for every v ∈ V (G)§, there exists w ∈ S such that dG(v, w) = 2 and S = V (G) or V (G)§ has no isolated vertex. The smallest cardinality of such a set, denoted by γrsRh(G), is called the restrained strong resolving hop domination number of G. In this paper, we obtained the corresponding parameter in graphs resulting from the join, corona and lexicographic product of two graphs. Specifically, we characterize the restrained strong resolving hop dominating sets in these types of graphs and determine the bounds or exact values of their restrained strong resolving hop domination numbers.